2011
DOI: 10.1016/j.ccc.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Acute Lung Injury: Insights into the Pathogenesis of Acute Lung Injury

Abstract: Studies of potential biomarkers in experimental models of acute lung injury (ALI) and from clinical samples from patients with ALI have provided extensive information relating to the pathophysiology of the mechanisms of lung injury and repair. The utility of biomarkers remains still solely part of the research tools to investigate lung injury and repair mechanisms and due to lack of sensitivity and specificity cannot yet be used as a clinical decision tool in patients with either acute lung injury or ARDS. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(192 citation statements)
references
References 158 publications
9
182
0
Order By: Relevance
“…The migration and accumulation of inflammatory factors and apoptotic factors can produce large amount of oxygen free radicals and protease, resulting in pulmonary capillary endothelial cell and alveolar epithelial cell injuries 11 and ultimately leads to cell apoptosis, causing ALI. Previous studies showed that many pro-inflammatory cytokines such as IL-8 and IL-6 contributed to the induction of ALI 12 . In the present study, we provided additional evidences that MIRI, on one hand, increased cell apoptosis in the lung; on the other hand, increased pro-inflammatory cytokines release (IL-6 and IL-8) and reduced anti-inflammatory cytokine (IL-10) release, resulting in enhanced inflammation in the lung, and caused ALI.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The migration and accumulation of inflammatory factors and apoptotic factors can produce large amount of oxygen free radicals and protease, resulting in pulmonary capillary endothelial cell and alveolar epithelial cell injuries 11 and ultimately leads to cell apoptosis, causing ALI. Previous studies showed that many pro-inflammatory cytokines such as IL-8 and IL-6 contributed to the induction of ALI 12 . In the present study, we provided additional evidences that MIRI, on one hand, increased cell apoptosis in the lung; on the other hand, increased pro-inflammatory cytokines release (IL-6 and IL-8) and reduced anti-inflammatory cytokine (IL-10) release, resulting in enhanced inflammation in the lung, and caused ALI.…”
Section: ■ Discussionmentioning
confidence: 99%
“…30,31 In the pathogenesis of ALI, extensive cytokines and ROS were released. 32 Inflammation initiated by oxidative stress can be regulated by the RvD1. 9 One of our previous studies on 15-epi-16-parafluorophenoxy lipoxin A4 (ATL), an analogue of RvD1, have found that ATL not only increased HO-1 expression but also markedly diminished all markers of lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Donnelly et al (41) noted that increased BAL IL-8 secretion and increased alveolar macrophage IL-8 expression was associated with progression to ARDS among at-risk patients with significant systemic inflammation. Additionally, increased BAL IL-8 was associated with increased mortality in patients with established ARDS (31,116,121).…”
Section: Macrophage Function During Human Ardsmentioning
confidence: 99%